Konsep Dasar Perancangan Agrarian Edu-Recreational Space di Desa Canggu, Provinsi Bali: Bahasa Indonesia - Made Yosia Sebastian Purwita; I Wayan Wirya Sastrawan; Ida Bagus Gede Parama Putra (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2024)
Agriculture, or agriculturalism, is one of Indonesia's regional identities. It is no surprise that a sizable number of domestic, local, and foreign tourists enjoy visiting the Canggu community in Bali Province because the community is particularly famous for its views of the nearby rice fields and has a strong agrarian culture. However, this exposure has greatly impacted residential construction and tourist destinations for domestic, international, and local tourists, which also poses a danger to neighborhood shops. In Canggu Village's agricultural area, there has also been a large annual decline in the amount of agricultural land, and if this trend continues, it is expected that agricultural land will eventually become extinct in the area. Therefore, it is necessary to take preventive steps to prevent this. Using three stages of research methods in the form of data collection, data processing, and data inference to capture the idea and concept about designing an area that assists in developing educational and recreational agriculture tourism for local and international communities also helps develop the local regional economy by providing a platform for the locals to shop.